A Band Enhanced Plasma Metamaterial Absorber Based on Triangular Ring-Shaped Resonators - Hai-Feng Zhang; Hao Zhang; Yi Yao; Jing Yang; Jia-Xuan Liu (IEEE Photonics Journal)
In this paper, a novel way is proposed to realize a broadband absorber, which is based on the plasma metamaterial with the triangular ring-shaped resonators. Each unit cell of the proposed absorber includes three layers, which are metal layer, dielectric layer, and solid-state plasma (SSP) layer, respectively. The top layer is composed of the truncated SSP triangular ring-shaped resonators and the SSP triangular patches, which are situated the middle of triangular rings. An SSP cylinder also is inserted between the central of each SSP triangular patch and the bottom metal layer. The absorption bandwidth can be covered from 11.76 to 14.43 GHz when the absorption rate is larger than 90%, which also is polarization-independent. In addition, the better performances can be realized under different incident angles. To explain the mechanism of high absorption, the electric field, the surface current distribution, and power loss density at different resonant frequencies are present. Moreover, the tunable absorption can be obtained in the proposed absorber while the performance of the absorber can be improved by exciting the different SSP resonators.